Economic Diplomacy of Manufacturing Companies in Plastic Sack Exports to Singapore - Shakila Dwi Rahmadani; Abid Rohman (Department of International Relations, Brawijaya University, 2026)
Economic diplomacy is generally understood as an instrument used by the state to achieve national economic interests through trade, investment, and international economic cooperation. However, the development of globalization shows that non-state actors, including corporations, also have an important role in supporting economic relations between countries. This study aims to analyze the implementation of economic diplomacy carried out by plastic sack manufacturing companies in supporting exports to Singapore. This research aims to identify the economic diplomacy strategies and practices carried out by companies, explain the role of companies as non-state actors in Indonesia-Singapore economic relations, and analyze the benefits obtained from these export activities. The research uses a qualitative approach with a case study method. Primary data was obtained through semi-structured interviews with the company's export division staff, while secondary data was obtained through literature studies, corporate documents, as well as international trade data. Data analysis was carried out using the concept of economic diplomacy developed by Rana and Okano-Heijmans. The results show that the company's economic diplomacy practices are realized through the use of industry association networks, business communication with trading partners, adjustments to export regulations, and maintenance of product quality to maintain long-term relationships with clients in Singapore. The findings of the study also show that companies can play a role as non-state actors that support the sustainability of Indonesia-Singapore economic relations through trade activities that have been going on consistently since 1985.